PENINGKATAN KEMAMPUAN MEMBACA HURUF HIJAIYAH MELALUI MEDIA BALOK HURUF - Thufeila, Thufeila; Tawil, Tawil; Laely, Khusnul (Universitas Muhammadiyah Magelang, 2014)
The purpose of this study was to find out the improvement of students’ reading ability in hijaiyah letters through alphabet cubes at Bustanul Athfal ‘Aisyiyah of Tirto Paremono, Magelang Regency.The study was considered as action research conducted within two cycles covering planning, acting, observing, and reflecting. The subjects were 9 students taken from Group B of the kindergarten. A performance assessment and recording were administered for the data collection. The data were analyzed using both qualitative and quantitative methods to find out the the improvement of reading ability in hijaiyah letters.The study revealed that the alphabet cubes could improve students’ reading ability in hijaiyah lettersat Bustanl Athfal ‘Aisyiyah of Tirto Paremono, Magelang Regency. The results of the assessments showed that the students passed only 59.72% of the reading aspects. It increased to 73.33% after the first cycle and 90.27% after the second cycle.